1998
DOI: 10.1095/biolreprod59.2.426
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Increases Ability of the Spermatozoa to Bind to the Human Zona Pellucida1

Abstract: Sperm-zona pellucida binding, a crucial step in the process of fertilization, takes place in vivo in the upper portion of the fallopian tube. The presence of GnRH-like peptides in the female and the male genital tract has been described. In this work, the effect of GnRH and related peptides upon sperm-zona pellucida binding ability was studied. Sperm aliquots, capacitated for 4.5 h, were incubated for 5 min with saline (control) or 20 nM of GnRH, C-terminal (1-5) or N-terminal (5-10) fragments of GnRH, Substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
7
35
0
1
Order By: Relevance
“…Other hormones affecting reproduction, such as GnRH and kisspeptin, have been found to exert a direct effect in the ovaries of several mammalian species by activating their cognate receptors. For instance, GnRH and its receptor are expressed in granulosa cells of developing follicles in the rat ovary (Whitelaw et al 1995) and may play an important role in oocyte maturation (Dekel & Shalgi 1987), follicular atresia or selection (Whitelaw et al 1995), and fertilization processes (Morales 1998). G-protein coupled receptor (GPR)54, a receptor for kisspeptin, has been found to be expressed in the human testis (Kotani et al 2001) and rat ovary (Castellano et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other hormones affecting reproduction, such as GnRH and kisspeptin, have been found to exert a direct effect in the ovaries of several mammalian species by activating their cognate receptors. For instance, GnRH and its receptor are expressed in granulosa cells of developing follicles in the rat ovary (Whitelaw et al 1995) and may play an important role in oocyte maturation (Dekel & Shalgi 1987), follicular atresia or selection (Whitelaw et al 1995), and fertilization processes (Morales 1998). G-protein coupled receptor (GPR)54, a receptor for kisspeptin, has been found to be expressed in the human testis (Kotani et al 2001) and rat ovary (Castellano et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that GnRH-like molecules may play either or both an endocrine or paracrine function in these extrapituitary tissues [35]. In accord with this, it was shown that GnRH and GnRH agonists enhanced bovine in vitro fertilization through an effect on the cumulus-oocyte complex [36] and that GnRH increased sperm binding to the human ZP by a direct effect on the sperm cells [37]. Moreover, we have shown that GnRH antagonists inhibited sperm-ZP binding in humans in a dose dependent manner [38].…”
Section: Introductionmentioning
confidence: 85%
“…As a result of freezing and thawing, these oocytes were never viable. Before use, the oocytes were cut to obtain two equal halves, or hemizonae [37,38,40,42,43].…”
Section: Source and Preparation Of Biological Materialsmentioning
confidence: 99%
“…GnRH and GnRH agonists have been shown to increase the cleavage rate of bovine oocytes (Funston & Seidel 1995). Moreover, GnRH enhanced sperm-zona pellucida binding ability, which is completely blocked by cotreatment with GnRH antagonist (Morales 1998). During the luteal phase, but not the follicular phase of the menstrual cycle, both GnRH mRNA and protein have been demonstrated in the human Fallopian tube, where spermatozoa and oocytes are deposited to form zygotes (Casan et al 2000).…”
Section: Physiological Role Of Ovarian Gnrhs/ Gnrhrs In Granulosa-lutmentioning
confidence: 99%